The impact of trauma exposure on the development of PTSD and psychological distress in a volunteer fire service. (December 2018) - Milligan-Saville, Josie; Choi, Isabella; Deady, Mark; Scott, Paul; Tan, Leona; Calvo, Rafael A.; Bryant, Richard A.; Glozier, Nicholas; Harvey, Samuel B.
Highlights: Cross-sectional survey of 459 members of an Australian volunteer fire service. Highest frequency or cumulative levels of trauma exposure increased risk of PTSD. Greatest odds of developing a mental disorder was being trapped or being assaulted. Abstract: Emergency service workers (ESWs) are at increased risk of trauma-related mental disorders. However, volunteer ESWs, who comprise the majority of firefighters in Western countries, have limited access to the necessary support services for mental health problems. This study aimed to examine the impact of the level and types of trauma exposure on the development of mental disorders in a volunteer fire service. Members of an Australian volunteer fire service ( N  = 459) completed a cross-sectional survey. Information on the number and types of distressing critical incidents involved within the last year was collected. Validated, self-report measures were used to determine probable post-traumatic stress disorder (PTSD) and psychological distress caseness. The risk of probable PTSD was significantly higher for those with the most frequent involvement with distressing incidents and the highest levels of cumulative trauma exposure. Being trapped in a dangerous situation or being assaulted by other people, resulted in the greatest odds of developing a mental disorder. Volunteer fire service members with the highest levels of trauma exposure and involvement with particular types of critical incidents are at elevated risk of mental health problems. The implications for the provision of psychological support measures amongst volunteer emergency services are discussed.